Abdominal Injuries in University of Port Harcourt Teaching Hospital - Dodiyi-Manuel, Amabra (Niger J Surg, 2015)
BACKGROUND: Abdominal injury is relatively common in both civilian and military casualties and remains a major source of morbidity and mortality. The mechanism of injury may be blunt or penetrating. Some would require operative intervention, whereas others may be managed conservatively. OBJECTIVE: The aim was to determine the pattern and outcome of management of abdominal injuries in the University of Port Harcourt Teaching Hospital (UPTH). PATIENTS AND METHODS: This was a prospective study of all patients with abdominal injuries seen and managed in UPTH over a 4-year period (from January 1, 2009 to December 31, 2012). Relevant data were recorded and analyzed using Statistical Package for Social Sciences version 16. RESULTS: Forty-five patients were seen during the study period. There were 40 males (88.9%) and five females (11.1%) making a male to female ratio of 8:1. Their ages ranged from 15 to 45 years with a mean of 27.8 ± 1.6 years and 21 to 30 years was the most commonly affected age group. The mechanism of injury was penetrating in 33 patients (73.3%) and blunt in 12 patients (26.7%). Thirty-four patients (75.6%) had an exploratory laparotomy after resuscitation, while 11 (24.4%) were managed conservatively. Small bowel was the most commonly injured organ following penetrating injury, seen in 14 patients (42.4%) while spleen was the most common in blunt injuries, seen in five patients (41.7%). The most common postoperative complication was surgical site infection, seen in four patients (8.9%). Two patients died giving a mortality rate of 4.4%. CONCLUSION: Gunshot to the abdomen is the most common cause of abdominal injury in UPTH. Serious campaign and legislation against militant and criminal activities would help to reduce the incidence.